Snowflake-Shaped ZnO Nanostructures-Based Gas Sensor for Sensitive Detection of Volatile Organic Compounds - Tianli Han; Xuexue Li; Xiaoman Zhang; Jinyun Liu; Jinjin Li (Advances in Condensed Matter Physics)
Volatile organic compounds (VOCs) have been considered severe risks to human health. Gas sensors for the sensitive detection of VOCs are highly required. However, the preparation of gas-sensing materials with a high gas diffusion performance remains a great challenge. Here, through a simple hydrothermal method accompanied with a subsequent thermal treatment, a special porous snowflake-shaped ZnO nanostructure was presented for sensitive detection of VOCs including diethyl ether, methylbenzene, and ethanol. The fabricated gas sensors exhibit a good sensing performance including high responses to VOCs and a short response/recovery time. The responses of the ZnO-based gas sensor to 100 ppm ethanol, methylbenzene, and diethyl ether are about 27, 21, and 11, respectively, while the response times to diethyl ether and methylbenzene are less than 10 seconds. The gas adsorption-desorption kinetics is also investigated, which shows that the gas-sensing behaviors to different target gases are remarkably different, making it possible for target recognition in practical applications.